The Effect of the Alert Husband Education Program on the Level of Husband Support for Pregnant Women at the Rum Balibunga Community Health Center, Tidore - Irmawati Naser; Rani Safitri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Husband support plays a crucial role in maternal health outcomes during pregnancy. This study aimed to analyze the effect of education using the Alert Husband Program on improving the level of husband support among pregnant women at the Rum Balibunga Community Health Center, Tidore. The study used a pre-experimental one-group pretest-posttest design with a sample of 28 husbands selected through total sampling. The research instrument was a structured questionnaire to measure emotional, informational, and instrumental support. The intervention was conducted through a 60-minute Alert Husband education program, which included presentation of material, interactive discussion, clarification, and joint conclusions. The results showed a significant increase in the level of husband support, from an average score of 45.32 to 62.89 (p = 0.000). The distribution of support categories also showed a significant shift towards better support after the intervention, with 57.2 % of husbands in the good support category. This study concluded that education through the Alert Husband Program was effective in improving husbands' understanding, attitudes, and involvement in supporting pregnant women, making it worthy of recommendation as an educational method in primary health care facilities.